Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2000
DOI: 10.1115/2000-gt-0619
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Design and Analysis of a High Pressure Ratio Aspirated Compressor Stage

Abstract: The pressure ratio of axial compressor stages can be significantly increased by controlling the development of blade and endwall boundary layers in regions of adverse pressure gradient by means of boundary layer suction. This concept is validated and demonstrated through the design and analysis of a unique aspirated compressor stage which achieves a total pressure ratio of 3.5 at a tip speed of 1500 ft/s. The aspirated stage was designed using an axisymmetric through-flow code coupled with a quasi three-dimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…Because of the large number of variables in the study, the inlet rotor face Mach number (M) is set to 0.65, and the flow coefficient is set to 0.475 and 0.89, two values representing the two designs proposed by Merchant in reference [14]. shows the maximum pressure ratio that can be achieved by a conventional design for # = .89 at the hub streamline is 1.55, and the maximum efficiency of 92% is achieved for a stage pressure ratio of 1.4.…”
Section: D14 Results With Radial Variations and Axial Velocity Ratiomentioning
confidence: 99%
See 3 more Smart Citations
“…Because of the large number of variables in the study, the inlet rotor face Mach number (M) is set to 0.65, and the flow coefficient is set to 0.475 and 0.89, two values representing the two designs proposed by Merchant in reference [14]. shows the maximum pressure ratio that can be achieved by a conventional design for # = .89 at the hub streamline is 1.55, and the maximum efficiency of 92% is achieved for a stage pressure ratio of 1.4.…”
Section: D14 Results With Radial Variations and Axial Velocity Ratiomentioning
confidence: 99%
“…1. Merchant [14]. The analysis shows a constant radial total pressure distribution for the rotor except for a small bump at the hub.…”
Section: Mises Designmentioning
confidence: 94%
See 2 more Smart Citations
“…Wu et al [10] used the total pressure ratio, mass flow and efficiency as an objective function and showed that pressure ratio and rotor loading can be improved further through optimizing swirl distribution using adaptive simulated annealing (ASA) algorithm. Merchant et al [11] demonstrated the possibility of substantially increasing the pressure ratio of a compressor stage at a given tip speed and increased the pressure ratio by controlling the development of blade and end-wall boundary layer in region of adverse pressure gradient by means of boundary layer suction.…”
Section: Introductionmentioning
confidence: 99%